Pengaruh Ekstrak Bawang Merah (Allium cepa L.) sebagai Zat Pengatur Tumbuh pada Benih Kakao (Theobroma cacao L.) - Paelongan, Agustinus Hermes; Malau, Krisna Margaretta; Semahu, La Hambui (Politeknik Negeri Lampung, 2023)
Cocoa (Theobroma cacao L.) is a beverage crop with high economic value. Provision of natural PGR, namely red unions, which will be extracted. This study aimed to determine the effect of red onionxtract (Allium cepa L.) as a growth regulator on cocoa seeds. The research was conducted at a screen house at the Polytechnic of Agricultural Development Manokwari (Politeknik Pembangunan Pertanian Manokwari). The study method used was a completely randomized design (CRD), using five treatments and 20 replications, so the number of samples was 100 seeds. The treatments tested on cocoa plant seeds P0 (control), P1 (25% concentration of red onion extract), P2 (50% concentration of red onion extract), P3 (75% concentration of red onion extract), and P4 (100% concentration of red onion extract). The measurement variables included germination percentage, plant height, stem diameter, number of leaves, and seedling growth percentage. Differences in the concentration of growth regulators of red onion extract had a significantly different effect on seedling percentage and seed growth percentage and had a significant effect on plant height, stem diameter, and number of leaves of cocoa seedlings. Soaked cocoa seeds in red union extract with a concentration of 25% give optimum results.